2013
DOI: 10.1371/journal.pone.0058325
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of DNA–Dependent Protein Kinase Promotes Heat–Induced Apoptosis Independently of Heat–Shock Protein Induction in Human Cancer Cell Lines

Abstract: The inhibition of DNA damage response pathway seems to be an attractive strategy for cancer therapy. It was previously reported that in rodent cells exposed to heat stress, cell growth was promoted by the activity of DNA-dependent protein kinase (DNA-PK), an enzyme involved in DNA non-homologous end joining (NHEJ) required for double-strand break repair. The absence of a functioning DNA-PK was associated with down regulation of heat shock protein 70 (HSP70). The objective of this study is thus to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…In the present study, GADD45B demonstrated increased mRNA levels in the EGR1-overexpressing H1299 cells. Several anti-apoptotic proteins, such as SON28, PRKDC29, and TOP130, were also downregulated in the EGR1-overexpressing cells, and several apoptotic proteins, including KRT1831, NR4A132, and TGM233, were upregulated in the same group of cells.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, GADD45B demonstrated increased mRNA levels in the EGR1-overexpressing H1299 cells. Several anti-apoptotic proteins, such as SON28, PRKDC29, and TOP130, were also downregulated in the EGR1-overexpressing cells, and several apoptotic proteins, including KRT1831, NR4A132, and TGM233, were upregulated in the same group of cells.…”
Section: Discussionmentioning
confidence: 88%
“…The second most frequently amplified gene (5/10 tumors) encodes the nuclear receptor NR1D1, a survival factor in a subset of breast cancers. Its driver effect might rely on its antiapoptotic activity [ 23 ] or on its known upregulation of genes involved in an abnormal aerobic glycolysis typical of cancer [ 24 ]. MMAB , found amplified in 4 out of 10 tumors, encodes the enzyme catalyzing the final step for conversion of vitamin B(12) into adenosylcobalamin.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in rodent cells exposed to heat stress indicated that cell growth was promoted by the activity of DNA-dependent protein kinase (DNA-PK) (Nueda et al 1999). The absence of a functioning DNA-PK is known to be associated with down-regulation of heat shock protein 70 (HSP70) (Okazawa et al 2013). This gene has also been identified as one of the functional candidates for mastitis resistance in cattle (Schwerin et al 2003).…”
Section: Discussionmentioning
confidence: 99%